Given the equation:
![y=x^3-3x^2-4x](https://img.qammunity.org/2023/formulas/mathematics/college/3rpxs0w76zvbyrgn22kmq5wekhy1l4sxce.png)
first notice that on the expression on the right, all the terms have at least one common factor x, then, we can write it as follows:
![x^3-3x^2-4x=x(x^2-3x-4)](https://img.qammunity.org/2023/formulas/mathematics/college/vxznu1pllf2oi0sh1aqkti7l9003gdindl.png)
then, the expression that we have between the parenthesis, can be factored as follows:
![x^2-3x-4=(x-4)(x+1)](https://img.qammunity.org/2023/formulas/mathematics/college/rvfztxl9bsljqlpdab16dcqzxw6ldo8egt.png)
then, the original equation can be factored like this:
![x^3-3x^2-4x=x(x-4)(x+1)](https://img.qammunity.org/2023/formulas/mathematics/college/s86oa17cwusfrw8w4ur1po0c04gw4bw7j6.png)
which has zeros x = 0, x = 4 and x = -1